Board Composition and Performance of Non-Governmental Organizations in Ethiopia - Lakachew Walie Zeleke; Wario Guyo; Makori Moronge (International Review of Social Sciences Research, 2023)
The objective of the study was to determine the influence of board composition on performance of non-governmental organizations (NGOs) in Ethiopia through descriptive survey and correlational research designs. The study achieved 72.6% response rate from 276 chief executives and 199 board chairpersons analysed through descriptive and inferential statistics. The findings showed a positive relationship between board composition and performance of local NGOs. The results also showed that majority of the boards are characterized by limited diversity (male dominated), lack clearly constituted board committees and challenged on enablers of board function (infrequent meetings). Nonetheless, board diversity, effectiveness of the boards in carrying out their functions, and the existence of board committees were all important factors for determining performance of NGOs. With these findings, the study recommends setting of clear eligibility criteria for board appointments/elections, setting term limits, holding regular elections, regular appraisal of board and CEOs performance, induction of new board members, providing clear terms of references and encouraging gender diversity. Since the study was based on views of the board chairpersons and chief executive officers, secondary data and assessments of the external stakeholders can be used to triangulate the findings.